Probing the molecular mechanism of kaempferol in relieving rheumatoid arthritis based on network pharmacology - Haomiao Liu; Huangying Lu; Xuefei Fan; Suhuan Chen; Xiaoyu Chen; Weilu Gao (Scientific Reports)
Abstract Kaempferol is an active compound found in traditional Chinese medicine epimedium soup, which exhibits potent anti-inflammatory and antioxidant properties. Nevertheless, the mechanism of action in rheumatoid arthritis remains unclear. This study constructed targets protein interaction networks by utilizing the String platform. The analysis of GO function and kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment was performed on key target genes. Target gene validation was conducted through microarray analysis. Molecular docking was employed to evaluate the relationship between kaempferol and various key targets. In vitro experiments were conducted to elucidate kaempferol’s mechanism of action on rheumatoid arthritis. Topological analysis of the protein protein interaction (PPI) network identified 10 core targets. Mitogen activated protein kinase 8 (MAPK8), peroxisome proliferator-activated receptor gamma (PPARG), and nuclear factor kappa-B (NF-kB) were all differentially expressed in the microarray dataset and all belonged to the target genes of kaempferol. Furthermore, kaempferol exhibited the highest binding affinity for MAPK8. In vitro cellular experiments demonstrated that kaempferol suppressed autophagy, and ameliorated abnormal proliferation and inflammation in rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS) cells by activating the MAPK8/NOD-like receptor protein 3(NLRP3) signaling pathway.